Experimental and numerical progressive failure analysis in open-hole tensile tests of quası-isotropic composite laminates - Ahmadvashaghbash, Sina. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
In this study, the progressive failure behavior of the Open-Hole Tension (OHT) specimens was analyzed by both numerical and experimental methods. The analysis of failure behavior of the notched composite laminates under tensile loading is carried out by implementing both intralaminar failure and delamination failure modes. For damage initiation of in-plane failure, Hashin’s failure criterion has been assigned into the model mainly due to its higher accuracy that can be obtained with a lower number of material properties. In conjunction with damage initiation, damage evolution law for in-plane failure was defined in terms of fracture energy with linear softening. Initiation and evolution of delamination as a result of shear or normal stresses in adjacent plies were based on the Cohesive Zone Model. Numerical and experimental benchmarking studies have been conducted to evaluate Mode I and Mode II interlaminar fracture toughness by performing Double Cantilever Beam and End-Notched Flexure tests. In the experimental part of the study, damage progression in composites was investigated with Acoustic Emission (AE) technique. Optical instruments have been used to obtain reliable correlations with damage modes and the AE events. On the other hand, Digital Image Correlation and in-situ edge observation are applied simultaneously during the tensile tests of notched quasi-isotropic laminates. Finally, results are compared with predictions of the finite element model. The model is considered to successfully predict the strength and damage modes of the OHT specimens.
Keywords: Laminated materials -- Testing.; Composite materials -- Testing.